Susceptibility Analysis in Several Mouse Strains Reveals Robust T-Cell Responses After Mycoplasma pneumoniae Infection in DBA/2 Mice - Tamiya, Shigeyuki; Yoshikawa, Eisuke; Suzuki, Koichiro; Yoshioka, Yasuo (Frontiers in Cellular and Infection Microbiology, 2021)
Mycoplasma pneumoniae (Mp) is a highly contagious respiratory pathogen responsible for human community-acquired pneumonia. The number of antibiotic-resistant Mp strains is increasing; therefore, to develop novel therapeutics, it is crucial to precisely understand the pathogenesis of mycoplasma pneumonia. Herein, we examined the susceptibility and response to Mp among eight inbred mouse strains. Following infection, the bacterial load in the bronchoalveolar lavage fluid (BALF) from DBA/2 mice was higher than that in the other tested strains such as BALB/c mice, which are frequently used in Mp research. In contrast, the numbers of CD45+ immune cells and neutrophils in BALF were comparable between BALB/c and DBA/2 mice, with lower numbers observed in C57BL/6J and CBA/N mice than in BALB/c mice. Among the tested strains, the BALF level of interleukin 12 subunit p40 was highest in DBA/2 mice; however, significant differences in other cytokines levels were not observed between BALB/c and DBA/2 mice. After Mp infection, Mp-specific Th1 and Th17 responses were significantly enhanced in DBA/2 mice when compared with BALB/c mice. Furthermore, prior infection with Mp increased the number of neutrophils in BALF after the reinfection of DBA/2 mice through an Mp-specific CD4+ T cell-dependent mechanism. Thus, DBA/2 may be an appropriate strain for evaluating Mp infection. Moreover, a comparison of responses revealed by various inbred mouse strains could be useful for elucidating the pathogenesis of Mycoplasma pneumonia.